New data on Galloisiana sinensis Wang, 1987 (Grylloblattodea: Grylloblattidae) with description of the hitherto unknown female - Zhou, Lin; Wang, Taoqi; Liu, Yi; Qi, Yuzhe; Chen, Qi; Ren, Bingzhong (Zootaxa, 2025)
Advanced microscopic imaging techniques were employed to systematically examine the morphological features of Galloisiana sinensis. The hitherto unknown female of G. sinensis is described and illustrated. The male of this species is also redescribed and illustrated. This investigation contributes useful new morphological data to the taxonomic investigation of Grylloblattidae. Several measures to update and strengthen the conservation of Grylloblattidae in China are suggested here: (1) Designate protected areas for Grylloblattidae to safeguard against habitat destruction; (2) Develop protocols for Grylloblattidae sample collection, establish a robust approval process, and prohibit unauthorized collection for any purpose; (3) Conduct systematic, long-term conservation surveys at representative distribution sites.